Utilization of Transcriptome, Small RNA, and Degradome Sequencing to Provide Insights Into Drought Stress and Rewatering Treatment in Medicago ruthenica - Shi, Rui; Jiao, Wei; Yun, Lan; Zhang, Zhiqiang; Zhang, Xiujuan; Wang, Quanzhen; Li, Ying; Mi, Fugui (Frontiers in Plant Science, 2021)
Drought is a major limiting factor in foraging grass yield and quality. Medicago ruthenica (M. ruthenica) is a high-quality forage legume with drought resistance, cold tolerance, and strong adaptability. In this study, we integrated transcriptome, small RNA, and degradome sequencing in identifying drought response genes, miRNAs, and key miRNA-target pairs in M. ruthenica under drought and rewatering treatment conditions. A total of 3,905 genes and 50 miRNAs (45 conserved and 5 novel miRNAs) were significantly differentially expressed in three test conditions (CK: control, DS: plants under drought stress, RW: plants rewatering after drought stress). The degradome sequencing (AllenScore < 4) analysis revealed that 104 miRNAs (11 novel and 93 conserved miRNAs) were identified with 263 target transcripts, forming 296 miRNA-target pairs in three libraries. There were 38 differentially expressed targets from 16 miRNAs in DS vs. CK, 31 from 11 miRNAs in DS vs. RW, and 6 from 3 miRNAs in RW vs. CK; 21,18, and 3 miRNA-target gene pairs showed reverse expression patterns in DS vs. CK, DS vs. RW, and RW vs. CK comparison groups, respectively. These findings provide valuable information for further functional characterization of genes and miRNAs in response to abiotic stress, in general, and drought stress in M. ruthenica, and potentially contribute to drought resistance breeding of forage in the future.